Occurrence of the S230R integrase strand inhibitor mutation in a treatment-naïve individual case report - Gudipati, Smitha (Medicine (Baltimore), 2020)
RATIONALE: Transmitted resistance to integrase strand inhibitors (INSTI) has been uncommon, but is slowly becoming more prevalent among those living with HIV. In an era with 2-drug regimens for antiretroviral therapy, transmitted resistance for INSTI is alarming. PATIENT CONCERNS: A 28-year-old African American female was recently diagnosed with HIV during a 30-week prenatal visit. DIAGNOSIS: HIV 4th generation test was positive as well as confirmation. Genotype was performed using next generation sequencing. INTERVENTIONS: Patient was initially rapidly started on a dolutegravir based regimen and changed to a protease inhibitor regimen once her genotype reported an S230R mutation. OUTCOMES: Patient became virally suppressed on antiretroviral therapy and delivered an HIV negative baby. LESSONS: INSTI resistance testing should be done for treatment-naïve and INSTI-naïve persons, particularly when considering 2 drug INSTI based regimens.